Reference values for body composition and physical fitness of young Brazilian elite soccer players - Portella, Daniel Leite; Vidal-Espinoza, Ruben; Sulla-Torres, Jose; Castelli Correia de Campos, Luis Felipe; Gomez-Campos, Rossana; Cossio-Bolaños, Marco (Frontiers in Physiology, 2023)
Objective: a) to verify whether body composition and physical fitness should be analyzed by chronological age and/or maturity stage in young Brazilian soccer players and b) to propose reference values for the evaluation of body composition and physical fitness by maturity stage in elite soccer players. Methods: A descriptive-correlational study was carried out in 206 young Brazilian soccer players (11 to 16 years old). The sample selection was non-probabilistic by convenience. Weight and standing height were evaluated. Body composition (BC) was assessed by dual X-ray absorptiometry (DXA). BC indicators [(percent fat (%F), Fat-free mass (FFM), Fat mass (FM) and Bone mass (BM)] were extracted. For physical fitness (PF), we applied the Flexibility (cm) sit and reach tests, explosive strength tests [Counter Movement Jump CMJ (cm) and horizontal jump HJ (cm)], speed [Speed 10m, 20m, 30 and 40m (seconds)] and Yo-Yo endurance level I test. Percentiles were constructed for BC and PF using the LMS method [L (Lambda; skewness), M (Mu; median) and S (Sigma; coefficient of variation)]. Results: The explanatory power between chronological age (CA) with BC was: FM (R2= 0.03%), FFM (R2= 0.66%) and BM (R2= 0.62%), while between maturity status (MS) with BC were: FM (R2= 0.04%), FFM (R2= 0.71%) and BM (R2= 0.66). The explanatory power between the CA with the physical fitness tests ranged from: (R2= 0.22 to 0.62%). While between MS with physical fitness the values ranged from: (R2= 0.23 to 0.64%). Percentiles per MS (P3, P5, P10, P15, P25, P50, P75, P85, P90, P95 and P97) were proposed for both BC and PF. Conclusion: The results of the study have shown that the evaluation of BC and PF of young soccer players should be performed by controlling for MS rather than for CA. The inclusion of a non-invasive method to control MS by means of percentiles during puberty may contribute to the development of retention and exclusion of young soccer players, thus, they may have a better chance of achieving sporting success.